Effects of resistance training frequency on muscle strength, activity and mass during a 24-week intervention in the elderly - Alonso Serrano, Javier (2016)
Elderly populations are increasingly affected by sarcopenia, dynapenia and osteoporosis. They all increase frailty and decrease quality of life and life-expectancy. Resistance training (RT) has been reported extensively as a tool that can prevent, counter and in some cases reverse the course of the abovementioned diseases. Several studies covering RT adaptations in elderly populations have investigated periods between 6 up to 88 weeks with different frequencies, from 1 to 3 trainings / week and a wide range of intensities (30-85% or one repetition maximum) and different volumes. The aim of this study was to investigate the effect of different training frequencies (one, two or three times / week) of periodized RT in older adults (60-75 years old) after a 36-week intervention period on strength adaptations and peak power, one repetition maximum dynamic leg press (1-RM) and explosive dynamic leg press with 50% of the 1-RM, muscle activity (measured by surface EMG, targeting vastus medialis and lateralis), lean mass (measured with Dual-energy X-ray absorptiometry) and basal serum hormones concentrations of testosterone (T), cortisol (COR), sex-hormone binding globulin (SHBG) and dehidroepiandrosterona (DHEA) . In this study, RT intervention significantly increased 1-RM, especially towards the highest frequency intervention groups (3 times / week in both men and women). Without correlating with frequency, T and COR concentrations increased and on the other hand, a significant decrease in SHBG/COR ratio was observed in both men and women. Once and twice / week frequencies bring up similar strength outcomes. RT is an appropriate tool for increasing strength in both older men and women.